PENGARUH YOUTUBE ADVERTISING TERHADAP RESPONS KONSUMEN - Arief Pratama; Rosita Anggraini (Inter Community: Journal of Communication Empowerment, 2019)
The purpose of this research is to study YouTube advertising research on consumer responses. The theory used is the theory of advertising value (informativeness, credibility, entertainment, irritation) and consumer response theory (awareness, knowledge, preferences, preferences, beliefs, purchases). This research is quantitative, while the research method is a survey with a type of explanatory research. The population in this study 344 people were students of STIKOM Interstudi year 2016-2017. To determine the sample size using the Slovin formula, collecting 100 respondents. The technique of answering data is done by closed question questionnaire, observation, literature, and literature study. While the data analysis technique is done by processing data using SPSS, analyzing data with statistical formulas and interpreting them. The results of this study are among YouTube advertisements on consumer responses showing strong results.